All solid state battery
By introducing a specific shape of voids into the positive and negative electrode layers of an all-solid state battery, the internal pressure caused by the expansion and contraction of the electrode material is alleviated, the problems of cracks and interface peeling are solved, and the internal resistance and cycling performance of the battery are improved.
Patent Information
- Application Number
- JP2021554205
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-23
- Filing Date
- 2020-09-29
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2040-09-29
AI Technical Summary
The internal pressure increase caused by the expansion and contraction of positive and negative electrodes during the charging and discharging of existing all-solid-state batteries can easily cause cracks and interface peeling, thereby increasing internal resistance and affecting cycling performance.
A specific shape of void is introduced into the positive and negative electrode layers, called a tapered asymmetric void, and its long axis direction is consistent with the expansion direction of the electrode material in the plane direction. This structure relieves internal pressure and reduces the occurrence of cracks and interface peeling.
It effectively reduces the internal pressure of all-solid-state batteries during charging and discharging, reduces the occurrence of cracks and interface peeling, thereby improving the internal resistance and cycling performance of the battery.
Smart Images

Figure 0007654555000004 
Figure 0007654555000005 
Figure 0007654555000006
Abstract
Description
[Technical field]
[0001] The present invention relates to an all-solid-state battery. This application claims priority based on Japanese Patent Application No. 2019-192583, filed on October 23, 2019, the contents of which are incorporated herein by reference. [Background technology]
[0002] In recent years, batteries have been used for various purposes. For example, batteries are used in portable batteries, and there is a demand for batteries to be small, lightweight, thin, and reliable. Batteries using electrolyte have problems such as electrolyte leakage and electrolyte depletion. Therefore, all-solid-state batteries using solid electrolytes have been attracting attention.
[0003] An all-solid-state battery has a positive electrode layer, a negative electrode layer, and a solid electrolyte layer. The positive electrode or the negative electrode expands and contracts when the all-solid-state battery is charged and discharged. The distortion caused by the expansion and contraction of the positive electrode or the negative electrode is one of the causes of cracks and is one of the causes of peeling at the lamination interface of each layer.
[0004] For example, Patent Document 1 discloses an all-solid-state battery having three solid electrolyte layers with different porosities between a positive electrode layer and a negative electrode layer. The three solid electrolyte layers with different porosities relieve internal stress and suppress the occurrence of cracks. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2013 / 175993 Summary of the Invention [Problem to be solved by the invention]
[0006] The cracks and interfacial peeling are one of the causes of an increase in internal resistance and a decrease in cycle characteristics.
[0007] Patent Document 1 describes a method for suppressing cracks. However, the structure is complicated and difficult to manufacture. In addition, the thickness in the stacking direction increases, which increases the thickness of the entire solid-state battery.
[0008] The present invention has been made in consideration of the above problems, and has an object to provide an all-solid-state battery capable of suppressing the occurrence of cracks and peeling at the laminate interface. [Means for solving the problem]
[0009] The inventors have found that by providing a void of a predetermined shape in the negative electrode layer or the positive electrode layer, which is the cause of the internal stress, the internal stress generated in the all-solid-state battery can be alleviated and the occurrence of cracks or interfacial peeling can be suppressed.
[0010] (1) An all-solid-state battery according to a first aspect includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, the positive electrode layer has a positive electrode current collector and a positive electrode active material layer in contact with the positive electrode current collector, the negative electrode layer has a negative electrode current collector and a negative electrode active material layer in contact with the negative electrode current collector, at least one of the positive electrode active material layer and the negative electrode active material layer has a plurality of voids therein, and the plurality of voids have anisotropic voids with an aspect ratio, calculated by dividing the length in the major axis direction by the length in the minor axis direction, of 2 or more and 29 or less.
[0011] (2) In the all-solid-state battery according to the above aspect, at least a portion of the side margin layers arranged adjacent to the outer periphery of the positive electrode layer and the negative electrode layer may have a plurality of voids therein, and the plurality of voids may have anisotropic voids having an aspect ratio, calculated by dividing the length in the major axis direction by the length in the minor axis direction, of 2 or more and 29 or less.
[0012] (3) In the all-solid-state battery according to the above aspect, 30% or more of the plurality of voids may be the anisotropic voids.
[0013] (4) In the all-solid-state battery according to the above aspect, a major axis direction of the anisotropic voids may substantially coincide with an in-plane direction in which the positive electrode active material layer or the negative electrode active material layer extends.
[0014] (5) In the all-solid-state battery according to the above aspect, the anisotropic voids may have an average length in the major axis direction of 0.2 μm or more and 40 μm or less, and an average length in the minor axis direction of the anisotropic voids may be 0.1 μm or more and 5 μm or less.
[0015] (6) In the all-solid-state battery according to the above aspect, the proportion of the plurality of voids in the positive electrode active material layer or the negative electrode active material layer may be 3% or more and 30% or less.
[0016] (7) The all-solid-state battery according to the above aspect may have an intermediate layer having ion conductivity between the solid electrolyte layer and at least one of the positive electrode layer and the negative electrode layer, and the intermediate layer may have a plurality of voids, and the proportion of the plurality of voids in the intermediate layer may be 0.1% or more and 8% or less. Effect of the Invention
[0017] The all-solid-state battery according to the above embodiment can suppress the occurrence of cracks and peeling at the laminate interface. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a schematic cross-sectional view of an all-solid-state battery according to an embodiment of the present invention. [Diagram 2] FIG. 2 is an enlarged view of a main part of the all-solid-state battery according to the present embodiment. [Diagram 3] FIG. 4 is an enlarged view of a main part of an all-solid-state battery according to a first modified example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present invention will be described in detail below with reference to the drawings as appropriate. The drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the features of the present invention easier to understand, and the dimensional ratios of each component may differ from the actual ones. The materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not limited thereto, and may be appropriately modified and implemented within the scope of the present invention.
[0020] First, the directions are defined. The direction in which the positive electrode layer 1 and the negative electrode layer 2 described later are stacked is defined as the z direction. One of the in-plane directions in which the positive electrode layer 1 and the negative electrode layer 2 described later extend is defined as the x direction, and the direction perpendicular to the x direction is defined as the y direction.
[0021] [All-solid battery] FIG. 1 is a schematic cross-sectional view of an enlarged portion of an all-solid-state battery according to the first embodiment. As shown in FIG. 1, the all-solid-state battery 10 has a laminate 4. The laminate 4 has a plurality of positive electrode layers 1, a plurality of negative electrode layers 2, and a solid electrolyte layer 3 located between the positive electrode layer 1 and the negative electrode layer 2. The positive electrode layer 1 is an example of a first electrode layer, and the negative electrode layer 2 is an example of a second electrode layer. One of the first electrode layer and the second electrode layer functions as a positive electrode, and the other functions as a negative electrode. The positive electrode layer 1 and the negative electrode layer 2 are connected to external terminals of corresponding polarities, respectively, and the positive electrode layer 1 and the negative electrode layer 2 are not in contact with each other.
[0022] The positive electrode layers 1 are each connected to a first external terminal 5, and the negative electrode layers 2 are each connected to a second external terminal 6. The first external terminal 5 and the second external terminal 6 are electrical contacts with the outside.
[0023] (Laminate) The laminate 4 has a plurality of positive electrode layers 1, a plurality of negative electrode layers 2, and a plurality of solid electrolyte layers 3. The solid electrolyte layer 3 is located between each of the positive electrode layers 1 and negative electrode layers 2. The all-solid-state battery 10 is charged and discharged by the exchange of lithium ions between the positive electrode layers 1 and the negative electrode layers 2 via the solid electrolyte layer 3.
[0024] "Positive and negative electrode layers" For example, there are a plurality of positive electrode layers 1 and a plurality of negative electrode layers 2 in the laminate 4. The positive electrode layers 1 and the negative electrode layers 2 are alternately laminated in the z direction with the solid electrolyte layer 3 sandwiched therebetween. Each positive electrode layer 1 and negative electrode layer 2 extends in the xy plane. A first end of the positive electrode layer 1 is connected to the first external terminal 5, and a second end thereof extends toward the second external terminal 6. A second end of the positive electrode layer 1 is not connected to the second external terminal 6. A first end of the negative electrode layer 2 is connected to the second external terminal 6, and a second end thereof extends toward the first external terminal 5. A second end of the negative electrode layer 2 is not connected to the first external terminal 5. A material similar to the solid electrolyte layer 3 exists between the positive electrode layer 1 and the second external terminal 6 and between the negative electrode layer 2 and the first external terminal 5.
[0025] The positive electrode layer 1 has a positive electrode current collector layer 1A and a positive electrode active material layer 1B. The negative electrode layer 2 has a negative electrode current collector layer 2A and a negative electrode active material layer 2B.
[0026] The positive electrode collector layer 1A and the negative electrode collector layer 2A extend in the xy plane. The positive electrode collector layer 1A and the negative electrode collector layer 2A contain a material having excellent electrical conductivity. The positive electrode collector layer 1A and the negative electrode collector layer 2A are portions containing 50% or more of a material having excellent electrical conductivity when the all-solid-state battery 10 is divided along the xy plane. Examples of the material having excellent electrical conductivity include silver, palladium, gold, platinum, aluminum, copper, and nickel. Copper does not easily react with the positive electrode active material, the negative electrode active material, and the solid electrolyte. For example, when copper is used for the positive electrode collector layer 1A and the negative electrode collector layer 2A, the internal resistance of the all-solid-state battery 10 can be reduced. The materials constituting the positive electrode collector layer 1A and the negative electrode collector layer 2A may be the same or different.
[0027] The positive electrode collector layer 1A may contain a positive electrode active material described later. The negative electrode collector layer 2A may contain a negative electrode active material described later. The content ratio of the active materials contained in each collector layer is not particularly limited as long as it functions as a collector. The volume ratio of the conductive material to the positive electrode active material in the positive electrode collector layer 1A is, for example, within a range of 90:10 to 70:30. Similarly, the volume ratio of the conductive material to the negative electrode active material in the negative electrode collector layer 2A is, for example, within a range of 90:10 to 70:30. When the positive electrode collector layer 1A and the negative electrode collector layer 2A contain a positive electrode active material and a negative electrode active material, respectively, the adhesion between the positive electrode collector layer 1A and the positive electrode active material layer 1B and the adhesion between the negative electrode collector layer 2A and the negative electrode active material layer 2B are improved.
[0028] The positive electrode active material layer 1B and the negative electrode active material layer 2B extend in the xy plane. The positive electrode active material layer 1B is formed on one or both sides of the positive electrode collector layer 1A. The positive electrode active material layer 1B may not be present on the surface of the positive electrode collector layer 1A on which the opposing negative electrode layer 2 is not present. The negative electrode active material layer 2B is formed on one or both sides of the negative electrode collector layer 2A. The negative electrode active material layer 2B may not be present on the surface of the negative electrode collector layer 2A on which the opposing positive electrode layer 1 is not present. For example, the positive electrode layer 1 or the negative electrode layer 2 located at the top or bottom of the laminate 4 may not have the positive electrode active material layer 1B or the negative electrode active material layer 2B on one side.
[0029] The positive electrode active material layer 1B and the negative electrode active material layer 2B contain active materials that donate and receive electrons during charging and discharging. The positive electrode active material layer 1B contains a positive electrode active material. The negative electrode active material layer 2B contains a negative electrode active material. The positive electrode active material layer 1B and the negative electrode active material layer 2B may each contain a conductive assistant, a binder, or the like. It is preferable that the positive electrode active material and the negative electrode active material can efficiently insert and extract lithium ions.
[0030] The positive electrode active material and the negative electrode active material are, for example, a transition metal oxide or a transition metal composite oxide. Specifically, the positive electrode active material and the negative electrode active material are, for example, a lithium manganese composite oxide Li2Mn a Ma 1-aO3 (0.8 ≤ a ≤ 1, Ma = Co, Ni), lithium cobaltate (LiCoO2), lithium nickelate (LiNiO2), lithium manganese spinel (LiMn2O4), general formula: LiNi x Co y Mn z O2 (x + y + z = 1, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1), a composite metal oxide represented by, lithium vanadium compound (LiV2O5), olivine type LiMbPO4 (where Mb is one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, Zr), lithium vanadium phosphate (Li3V2(PO4)3, Li2VTi(PO4)3, LiVOPO4), Li2MnO3 - LiMcO2 (Mc = Mn, Co, Ni) represented by an Li-excess solid solution cathode, lithium titanate (Li4Ti5O 12 )、Li s Ni t Co u Al v O2 (0.9 < s < 1.3, 0.9 < t + u + v < 1.1), and the like, a composite metal oxide represented by.
[0031] There is no clear distinction between the active materials constituting the positive electrode active material layer 1B or the negative electrode active material layer 2B. By comparing the potentials of the two types of compounds, the compound showing a more noble potential can be used as the positive electrode active material, and the compound showing a more base potential can be used as the negative electrode active material.
[0032] At least one of the positive electrode active material layer 1B and the negative electrode active material layer 2B has a plurality of voids inside. FIG. 2 is an enlarged schematic view of the vicinity of the interface between the positive electrode layer 1 and the solid electrolyte layer 3 of the all-solid-state battery 10 according to the present embodiment. The positive electrode active material layer 1B shown in FIG. 2 has a plurality of voids V. In FIG. 2, the positive electrode active material layer 1B is illustrated, but the negative electrode active material layer 2B may have a plurality of voids V, or both the positive electrode active material layer 1B and the negative electrode active material layer 2B may have a plurality of voids V.
[0033] A plurality of voids V are formed between the active materials constituting the positive electrode active material layer 1B or the negative electrode active material layer 2B. Since the active material is responsible for the conduction of electrons during charging and discharging, it is common to densely pack the active material in the positive electrode active material layer 1B and the negative electrode active material layer 2B. The plurality of voids V are intentionally provided.
[0034] The proportion of the voids V in the positive electrode active material layer 1B or the negative electrode active material layer 2B (hereinafter referred to as the area ratio of the voids V) is, for example, 3% or more and 30% or less. The area ratio of the voids V is calculated, for example, as the average value of the area ratios of black regions when each of a plurality of cross-sectional images obtained by a scanning electron microscope (SEM) is binarized. Hereinafter, a specific method for calculating the area ratio of the voids V will be described using an example in which a plurality of voids V exists in the positive electrode active material layer 1B.
[0035] First, five images each of the xz cross section and the yz cross section of the positive electrode active material layer 1B are taken. The area of the positive electrode active material layer 1B is calculated from each image. In an actual SEM image, the interface between the positive electrode collector layer 1A and the positive electrode active material layer 1B and the interface between the positive electrode active material layer 1B and the solid electrolyte layer 3 are not flat. Therefore, the area of the positive electrode active material layer 1B is converted to the area of the region sandwiched between the xy plane extending at the average height position of the interface between the positive electrode collector layer 1A and the positive electrode active material layer 1B and the xy plane extending at the average height position of the interface between the positive electrode active material layer 1B and the solid electrolyte layer 3.
[0036] Next, the area of the multiple voids V in each image is obtained. The area of the multiple voids V can be obtained, for example, by the following procedure. First, the luminance of the conductive material portion of the positive electrode collector layer 1A and the luminance of the multiple voids V are extracted from each of the captured images. The conductive material portion of the positive electrode collector layer 1A is white and is considered to be the upper luminance limit of each image. The multiple voids V are black and are considered to be the lower luminance limit of each image. The range of luminance in each image is between the upper luminance limit and the lower luminance limit. Next, each image is binarized using a luminance that is 5% of the luminance range from the lower luminance limit of each image on the upper luminance limit side as a threshold value (hereinafter, the image after binarization is referred to as a binarized image). In the binarized image, a portion with a luminance lower than the threshold value becomes a black area, and a portion with a luminance higher than the threshold value becomes a white area. The area of the black area in the binarized image becomes the area of the multiple voids V. Then, the area ratio of the positive electrode active material layer 1B of the plurality of voids V in each image is obtained, and the average value is calculated to obtain the area ratio of the plurality of voids V. Note that it is difficult to properly confirm anisotropic voids V1 having a major axis size of 50 nm or less using an SEM (magnification range of 500x to 5000x), and therefore these are excluded when measuring the area ratio, the ratio of anisotropic voids V1 to the plurality of voids, and the size of anisotropic voids V1, which will be described later.
[0037] At least one of the multiple voids V is an anisotropic void V1. The anisotropic void V1 preferably accounts for 30% or more of the multiple voids V, more preferably 50% or more, and even more preferably 80% or more. The anisotropic void V1 is a void having an aspect ratio, calculated by dividing the length in the major axis direction by the length in the minor axis direction, of 2 or more and 29 or less.
[0038] In FIG. 2, the anisotropic void V1 is illustrated as a schematic ellipse. However, the shape of the anisotropic void V1 does not matter. The anisotropic void V1 is, for example, indefinite. When the void is indefinite, a predetermined ellipse that has the smallest area that contains one black region in a binarized image is assumed to be the shape of the void, and the major axis length and minor axis length of the assumed ellipse are set to the major axis length and minor axis length of the void. Here, the ellipse that is assumed to be the shape of the void is determined as follows. Among the ellipses that contain the ellipse with the smallest area, when the major axis length LLe of the ellipse is superimposed on the length LLc of the void V in the direction that is the longest (LLe=LLC), the ellipse with the shortest minor axis length SLe is assumed to be the shape of the void.
[0039] The average length of the anisotropic voids V1 in the long axis direction is, for example, 0.2 μm or more and 100 μm or less, and preferably 0.2 μm or more and 40 μm or less. The average length of the anisotropic voids V1 in the short axis direction is, for example, 0.1 μm or more and 50 μm or less, preferably 0.1 μm or more and 20 μm or less, and more preferably 0.1 μm or more and 5 μm or less. When there are multiple anisotropic voids V1, the average lengths of the anisotropic voids V1 in the long axis direction and the short axis direction are calculated by extracting two anisotropic voids V1 from each of the above-mentioned 10 binarized images and averaging the total of 20 anisotropic voids V1.
[0040] In addition, the anisotropic voids V1 are preferably oriented in the xy plane. "Oriented in the xy plane" means that the long axis direction of the anisotropic voids V1 is inclined at 45 degrees or more from the z direction. In addition, the long axis direction of the anisotropic voids V1 is preferably approximately aligned with the in-plane direction in which the xy plane extends. "The long axis direction of the anisotropic voids V1 is approximately aligned with the in-plane direction" means that the inclination angle of the long axis direction of the anisotropic voids V1 with respect to the xy plane is 10 degrees or less.
[0041] "Solid electrolyte layer" The solid electrolyte layer 3 is located between each of the positive electrode layer 1 and the negative electrode layer 2. As will be described later, side margin layers 11, 12 made of the same material as the solid electrolyte layer 3 may be provided between the positive electrode layer 1 and the second external terminal 6 and between the negative electrode layer 2 and the first external terminal 5.
[0042] The solid electrolyte layer 3 includes a solid electrolyte. The solid electrolyte is a substance (e.g., particles) that can move ions by an externally applied electric field. For example, lithium ions move within the solid electrolyte by an externally applied electric field. The solid electrolyte is also an insulator that inhibits the movement of electrons.
[0043] The solid electrolyte contains, for example, lithium. The solid electrolyte may be, for example, any of oxide-based materials and sulfide-based materials. The solid electrolyte may be, for example, any of perovskite-type compounds, lysicone-type compounds, garnet-type compounds, nasicon-type compounds, thiolisicone-type compounds, glass compounds, and phosphate compounds. La 0.5 Li 0.5 TiO3 is an example of a perovskite compound. 14 Zn(GeO4)4 is an example of a lysicone-type compound. i7 La3Zr2O 12 is an example of a garnet-type compound. LiZr2(PO4)3, Li 1.3 Al 0.3 Ti 1.7 (PO4) 3、 Li 1.5 Al 0.5 Ge 1.5 (PO4)3, Li 1.55 Al 0.2 Zr 1.7 S 0.25 P 9.75 O 12 , Li 1.4 Na 0.1 Zr 1.5 Al 0.5 (PO4)3, Li 1.4 Ca 0.25 Er 0.3 Zr 1.7 (PO4) 3.2 , Li 1.4 Ca 0.25Yb 0.3 Zr 1.7 (PO4) 3.2 is an example of a Nasicon-type compound. 3.25 Ge 0.25 P 0.75 S 4、 Li3PS4 is an example of a thiolisicone-type compound. Li2S-P2S 5、 Li2O-V2O5-SiO2 is an example of a glass compound. Li3PO4, Li 3.5 S 0.5 P 0.5 O4, Li 2.9 PO 3.3 N 0.46 is an example of a phosphate compound. The solid electrolyte may contain one or more of these compounds.
[0044] The shape of the solid electrolyte is not particularly limited. The shape of the solid electrolyte may be, for example, spherical, ellipsoidal, needle-like, plate-like, scaly, tubular, wire-like, rod-like, or amorphous. The particle size of the solid electrolyte may be, for example, 0.1 μm or more and 10 μm or less, and may be 0.3 μm or more and 9 μm or less. The particle size of the particles is determined from the measured value (D50) obtained by particle size distribution measurement. D50 is the diameter of the particles at which the integrated value in the distribution curve obtained by particle size distribution measurement is 50%. The particle size distribution of the particles is measured, for example, by a particle size distribution measuring device using a laser diffraction / scattering method (microtrack method).
[0045] "Side margin layer" 1, the laminate 4 includes side margin layers 11 and 12 that contain a solid electrolyte and are disposed adjacent to and around the outer periphery of the positive electrode layer 1 and the negative electrode layer 2. The side margin layers 11 and 12 are sometimes referred to as the positive electrode side margin layer and the negative electrode side margin layer, respectively.
[0046] The solid electrolyte contained in the side margin layers 11 and 12 may be the same as or different from the solid electrolyte contained in the solid electrolyte layer 3 .
[0047] The side margin layers 11 and 12 are preferably provided to eliminate the step between the solid electrolyte layer 3 and the positive electrode layer 1, and the step between the solid electrolyte layer 3 and the negative electrode layer 2. Therefore, the side margin layers 11 and 12 are formed in the main surface of the solid electrolyte layer 3 in an area other than the positive electrode layer 1 and the negative electrode layer 2, at substantially the same height as the positive electrode layer 1 or the negative electrode layer 2 (i.e., arranged next to the positive electrode layer 1 and the negative electrode layer 2, respectively). The presence of the side margin layers 11 and 12 eliminates the step between the solid electrolyte layer 3 and the positive electrode layer 1, and between the solid electrolyte layer 3 and the negative electrode layer 2, so that the density of the solid electrolyte 3 and each electrode layer is increased, and delamination and warping due to firing of the all-solid-state battery are less likely to occur.
[0048] At least some of the side margin layers 11, 12 may have a plurality of voids therein. When the side margin layers 11, 12 do not have a plurality of voids therein, the side margin layers 11, 12 may have the same configuration as the solid electrolyte layer 3. It is preferable that both of the side margin layers 11, 12 have a plurality of voids therein. The configuration of the plurality of voids contained in the side margin layers 11, 12 may be similar to the plurality of voids V contained in at least one of the positive electrode active material layer 1B and the negative electrode active material layer 2B.
[0049] At least one of the plurality of voids is an anisotropic void. The anisotropic voids preferably account for 30% or more of the plurality of voids contained in the side margin layer, more preferably 50% or more, and even more preferably 80% or more. The anisotropic void is a void having an aspect ratio, calculated by dividing the length in the major axis direction by the length in the minor axis direction, of 2 or more and 29 or less.
[0050] The proportion of the voids in the side margin layers 11 and 12 (hereinafter referred to as the area ratio of the voids in the side margin layers) is, for example, 3% or more and 30% or less. The area ratio of the voids in the side margin layers is determined in the same manner as the area ratios of the voids in the positive electrode active material 1B and the negative electrode active material 2B, for example, as the average area ratio of black regions when each of a plurality of cross-sectional images obtained by a scanning electron microscope (SEM) is binarized.
[0051] (Terminal) For example, a material having excellent electrical conductivity is used for the first external terminal 5 and the second external terminal 6. For example, the first external terminal 5 and the second external terminal 6 are any of silver, gold, platinum, aluminum, copper, tin, and nickel. The first external terminal 5 and the second external terminal 6 may be a single layer or multiple layers.
[0052] (protective layer) The all-solid-state battery 10 may have a protective layer on the outer periphery for electrically, physically, and chemically protecting the laminate 4 and the terminals. The protective layer is preferably made of a material that is excellent in insulation, durability, and moisture resistance and is environmentally safe. The protective layer is, for example, glass, ceramics, thermosetting resin, or photocurable resin. The protective layer may be made of one type of material or a combination of two or more types of materials. The protective layer may be a single layer or multiple layers. The protective layer is preferably an organic-inorganic hybrid made by mixing a thermosetting resin and ceramic powder.
[0053] Next, a method for producing the all-solid-state battery according to this embodiment will be described. The all-solid-state battery 10 may be produced by a co-firing method or a sequential firing method. The co-firing method is a method in which materials forming each layer are laminated and then sintered all at once. The sequential firing method is a method in which each layer is fired after being laminated. The co-firing method has a simpler process than the sequential firing method. In addition, the laminate 4 produced by the co-firing method is denser than the laminate 4 produced by the sequential firing method. Below, an example of using the co-firing method will be described.
[0054] First, pastes for each layer constituting the laminate 4 are prepared. The materials for the positive electrode collector layer 1A, the positive electrode active material layer 1B, the solid electrolyte layer 3, the side margin layers 11 and 12, the negative electrode active material layer 2B, and the negative electrode collector layer 2A are each made into a paste. The method of making the paste is not particularly limited. For example, the paste is obtained by mixing the powder of each material with a vehicle. The vehicle is a general term for a medium in a liquid phase. The vehicle includes a solvent and a binder.
[0055] A filler is added to the voids of at least one of the positive electrode active material layer 1B and the negative electrode active material layer 2B. When voids are included inside the side margin layers 11 and 12, a filler is also added to the voids of the side margin layers 11 and 12. The filler is, for example, a binder remover, a resin material, or a carbon material. All of the fillers volatilize during firing. The carbon material used as the filler volatilizes during firing and can be distinguished from the conductive assistant. The filler is, for example, flake graphite, amorphous carbon, or a pore former. The pore former is, for example, a resin particle such as polyethylene, polypropylene, or polyethylene terephthalate. The filler has an anisotropic shape. The aspect ratio, which is the length of the filler in the major axis direction divided by the length of the minor axis direction, is, for example, 2 or more and 29 or less. The filler becomes anisotropic voids V1 by volatilizing during firing. The size of the filler to be added is determined by the shrinkage of the active material due to firing, and the size of the voids also shrinks. The size of the filler is calculated backwards from the shrinkage rate of the active material, and made larger than the target void size. For example, if the shrinkage rate due to firing is 0.8, to form voids with a diameter of 4 μm, the calculation is 4 μm ÷ 0.8 = 5 μm, so a filler with a diameter of 5 μm is added.
[0056] Next, a green sheet is prepared. The green sheet is obtained by processing the paste into a sheet shape. For example, the paste is applied to a substrate such as PET (polyethylene terephthalate) in a desired order, dried as necessary, and then peeled off from the substrate to obtain the green sheet. The method of applying the paste is not particularly limited. For example, known methods such as screen printing, application, transfer, doctor blade, etc. can be adopted.
[0057] When preparing the green sheets for the positive electrode active material layer 1B and the negative electrode active material layer 2B, the filler can be oriented in the xy in-plane direction by controlling the coating speed or coating through a mesh having openings. When the filler is oriented in the xy in-plane direction, the anisotropic voids V1 are oriented in the xy in-plane direction in the prepared positive electrode active material layer 1B and negative electrode active material layer 2B.
[0058] The green sheets thus produced are stacked in a desired order and number of layers. Alignment, cutting, etc. are performed as necessary to produce a laminate. When producing a parallel or series-parallel battery, the positive and negative current collector layers are aligned so that the end faces of the positive and negative current collector layers do not coincide with each other.
[0059] The laminate may be produced after preparing the positive electrode active material layer unit and the negative electrode active material layer unit described below.
[0060] First, the paste for the solid electrolyte layer is formed into a sheet shape on a PET film by a doctor blade method and dried. Next, the paste for the positive electrode active material layer is printed on the green sheet for the solid electrolyte layer by screen printing and dried. Then, the paste for the side margin layer is screen printed on the area of the solid electrolyte layer sheet other than the positive electrode layer and dried to form a side margin layer with approximately the same height as the positive electrode layer.
[0061] Next, the paste for the positive electrode collector layer is printed by screen printing on the dried paste for the positive electrode active material layer and dried. The paste for the positive electrode collector layer is printed again by screen printing on the dried paste for the positive electrode collector layer and dried. Then, the PET film is peeled off to produce a positive electrode unit. The positive electrode unit has a positive electrode layer 1 in which a positive electrode active material layer 1B / a positive electrode collector layer 1A / a positive electrode active material layer 1B are laminated in this order on the main surface of a solid electrolyte layer 3, and a side margin layer 11 is formed.
[0062] The negative electrode unit is also produced by the same procedure. The negative electrode unit has a negative electrode layer 2, which is formed by laminating a negative electrode active material layer 2B / a negative electrode current collector layer 2A / a negative electrode active material layer 2B in this order on the main surface of a solid electrolyte layer 3, and a side margin layer 12.
[0063] Next, the positive electrode unit and the negative electrode unit are stacked. The positive electrode unit and the negative electrode unit are stacked so that the solid electrolyte layers of the respective units do not face each other. The stacked laminate is stacked in the order of positive electrode active material layer 1B / positive electrode current collector layer 1A / positive electrode active material layer 1B / solid electrolyte layer 3 / negative electrode active material layer 2B / negative electrode current collector layer 2A / negative electrode active material layer 2B / solid electrolyte layer 3. The positive electrode unit and the negative electrode unit are stacked with a shift so that the positive electrode current collector layer 1A is exposed on a first end face of the laminate and the negative electrode current collector layer 2A is exposed on a second end face opposite to the first end face. For example, a solid electrolyte layer sheet of a predetermined thickness is further stacked on the top layer and the bottom layer in the stacking direction and dried.
[0064] Next, the produced laminate is pressure-bonded together. The pressure-bonding is performed while heating. The heating temperature is, for example, 40 to 95°C. Next, the pressure-bonded laminate is sintered. For example, the sintering is performed by heating in a temperature range of 500°C to 1000°C in a nitrogen atmosphere. The sintering time is, for example, 0.1 to 3 hours. The laminate 4 is obtained by sintering. At this time, the filler becomes anisotropic voids V1.
[0065] The sintered body may be placed in a cylindrical container together with an abrasive such as alumina and barrel-polished. The corners of the sintered body are chamfered by polishing. Polishing may also be performed by sandblasting or the like.
[0066] Finally, a first external terminal 5 and a second external terminal 6 are attached to the laminate 4. The first external terminal 5 and the second external terminal 6 are formed so as to be in electrical contact with the positive electrode current collector layer 1A or the negative electrode current collector layer 2A, respectively. For example, the first external terminal 5 is connected to the positive electrode current collector layer 1A exposed from the side surface of the laminate 4, and the second external terminal 6 is connected to the negative electrode current collector layer 2A exposed from the side surface of the laminate 4. The first external terminal 5 and the second external terminal 6 can be produced by, for example, a sputtering method, a dipping method, a spray coating method, or the like.
[0067] In the all-solid-state battery according to the present embodiment, at least one of the positive electrode active material layer 1B and the negative electrode active material layer 2B has anisotropic voids V1 therein, thereby making it possible to suppress the occurrence of cracks and peeling at the lamination interface. The active materials contained in the positive electrode active material layer 1B and the negative electrode active material layer 2B expand and contract during charging and discharging. The volume change of the active material generates internal stress, which can cause cracks and interface peeling, but the anisotropic voids V1 function as a buffer to suppress the occurrence of cracks and interface peeling.
[0068] When the aspect ratio of the anisotropic void V1 is less than 2, the shape of the void becomes approximately isotropic. Pressure is applied evenly to the approximately isotropic void, and the void cannot adequately function as a buffer for the volumetric change of the active material. In contrast, the anisotropic void V1 is easily crushed in the minor axis direction due to the anisotropy of its shape, and is therefore unable to adequately buffer the volumetric change of the active material. In addition, when the aspect ratio of the anisotropic void V1 is greater than 29, distortion is concentrated in the active material adjacent to the void, and cracks are more likely to occur in the active material adjacent to the void.
[0069] The positive electrode active material layer 1B and the negative electrode active material layer 2B expand and contract mainly in the z direction. When the anisotropic voids V1 are oriented in the xy plane, the short axis direction of the anisotropic voids V1 becomes the z direction. The anisotropic voids V1 are easily crushed in the short axis direction, and by having the short axis direction of the anisotropic voids V1 become the z direction, cracks and interfacial peeling can be more effectively suppressed.
[0070] Furthermore, extremely large anisotropic voids V1 can cause cracks, etc. When the length of the anisotropic voids V1 in the major axis direction is 0.2 μm or more and 40 μm or less, and the length of the anisotropic voids V1 in the minor axis direction is 0.1 μm or more and 5 μm or less, cracks and interfacial peeling can be more effectively suppressed.
[0071] Furthermore, when the area ratio of the plurality of voids V is 3% or more and 30% or less, it is possible to suppress the capacity reduction of the all-solid-state battery while suppressing the occurrence of cracks and interfacial peeling.
[0072] The above describes the embodiments of the present invention in detail with reference to the drawings. However, each configuration and combination thereof in each embodiment is merely an example, and addition, omission, substitution, and other modifications of the configuration are possible without departing from the spirit of the present invention.
[0073] (First Modification) Fig. 3 is an enlarged cross-sectional view of a main part of the all-solid-state battery according to the first modified example. Fig. 3 is an enlarged view of the vicinity of the interface between the cathode layer 1 and the solid electrolyte layer 3 of the all-solid-state battery. The all-solid-state battery shown in Fig. 3 differs from the all-solid-state battery shown in Fig. 2 in that it has an intermediate layer 7 between the cathode layer 1 and the solid electrolyte layer 3. Although Fig. 3 shows an example in which the intermediate layer 7 is between the cathode layer 1 and the solid electrolyte layer 3, the intermediate layer 7 may be between the anode layer 2 and the solid electrolyte layer 3.
[0074] The intermediate layer 7 extends in the xy plane and is located between the positive electrode active material layer 1B or the negative electrode active material layer 2B and the solid electrolyte layer 3. The intermediate layer 7 is a layer having a composition between the active material constituting the positive electrode active material layer 1B or the negative electrode active material layer 2B and the solid electrolyte constituting the solid electrolyte layer 3. For example, when the positive electrode active material layer 1B or the negative electrode active material layer 2B is lithium vanadium phosphate (Li3V2(PO4)3, LiVOPO4) and the solid electrolyte is lithium zirconium phosphate (LiZr2(PO4)3), the intermediate layer 7 is lithium zirconium phosphate containing vanadium or lithium vanadium phosphate containing zirconium. The lithium zirconium phosphate containing vanadium is lithium zirconium phosphate in which part of the zirconium in lithium vanadium phosphate is replaced with vanadium. The lithium vanadium phosphate containing zirconium is lithium vanadium phosphate in which part of the vanadium in lithium vanadium phosphate is replaced with zirconium. The intermediate layer 7 increases the bonding strength between the positive electrode active material layer 1B or the negative electrode active material layer 2B and the solid electrolyte layer 3.
[0075] The intermediate layer 7 may have, for example, a plurality of voids V2. The proportion of the plurality of voids V2 in the intermediate layer 7 is preferably 0.1% or more and 8% or less. When the intermediate layer 7 also has a plurality of voids V2, the internal stress caused by the expansion and contraction of the active material can be alleviated, and the occurrence of cracks and interfacial peeling can be more effectively suppressed. Furthermore, when the proportion of the plurality of voids V2 in the intermediate layer 7 is not too high, the bonding strength between the positive electrode active material layer 1B or the negative electrode active material layer 2B and the solid electrolyte layer 3 can be maintained, and the occurrence of interfacial peeling can be more effectively suppressed.
[0076] The intermediate layer 7 is obtained by separately preparing a layer whose constituent elements have been adjusted in advance, and inserting the layer between the solid electrolyte layer 3 and the positive electrode active material layer 1B or the negative electrode active material layer 2B. The sintering conditions may be adjusted to thermally diffuse the constituent element of the solid electrolyte layer 3 (e.g., zirconium) into the positive electrode active material layer 1B or the negative electrode active material layer 2B, or to thermally diffuse the constituent element of the positive electrode active material layer 1B or the negative electrode active material layer 2B (e.g., vanadium) into the solid electrolyte layer 3.
[0077] The all-solid-state battery according to the first modification has the same effects as the all-solid-state battery according to the first embodiment. In addition, the intermediate layer 7 increases the bonding strength between the positive electrode active material layer 1B or the negative electrode active material layer 2B and the solid electrolyte layer 3, and can more effectively suppress the occurrence of interfacial peeling. EXAMPLES
[0078] Example 1 The all-solid-state battery of Example 1 was fabricated as follows.
[0079] (Preparation of active material) The active material used was lithium vanadium phosphate, which was prepared by the following method. Starting materials were Li2CO3, V2O5, and NH4H2PO4, which were wet mixed in a ball mill for 16 hours. The powder obtained after dehydration and drying was calcined in a nitrogen-hydrogen mixed gas at 850°C for 2 hours. The calcined product was wet-pulverized in a ball mill, and then dehydrated and dried to obtain the active material. An X-ray diffraction device was used to confirm that the powder produced had the same crystal structure as Li3V2(PO4)3.
[0080] (Preparation of Paste for Active Material Layer) The active material layer paste was prepared by adding 95 parts of the obtained active material powder, 2 parts of filler (polyethylene), 3 parts of flat carbon material (artificial graphite: TIMREX (registered trademark) Graphite KS-6L) powder, 15 parts of ethyl cellulose as a binder, and 65 parts of dihydroterpineol as a solvent, and mixing and dispersing them to prepare a positive electrode active material layer paste and a negative electrode active material layer paste. The filler used had a long axis length of 0.63 μm, a short axis length of 0.13 μm, and an aspect ratio of 5.0.
[0081] (Preparation of solid electrolyte) As a solid electrolyte, the LZP-based Nasicon-type compound (e.g. LiZr 1.7 Ca 0.3(PO4)3) was used. Li2CO3, ZrO2, CaCO3, and NH4H2PO4 were used as starting materials, and were wet mixed in a ball mill for 16 hours, then dehydrated and dried, and the resulting powder was calcined in air at 900°C for 2 hours. After calcination, the powder was wet ground in a ball mill for 16 hours, and then dehydrated and dried to obtain a solid electrolyte powder. It was confirmed using an X-ray diffraction device (XRD) that the crystal structure of the powder produced was the same as that of the LZP-based Nasicon-type compound.
[0082] (Preparation of paste for solid electrolyte layer) The solid electrolyte layer paste was prepared by adding 100 parts of solid electrolyte powder, 100 parts of ethanol and 200 parts of toluene as solvents, and wet mixing them in a ball mill. Then, 16 parts of a polyvinyl butyral binder and 4.8 parts of benzyl butyl phthalate were further added and mixed to prepare the solid electrolyte layer paste.
[0083] (Preparation of sheets for solid electrolyte layer) The paste for the solid electrolyte layer was formed into a sheet using a doctor blade method with a PET film as a substrate to obtain a sheet for the solid electrolyte layer having a thickness of 15 μm.
[0084] (Preparation of paste for current collector layer) To prepare a positive electrode current collector and a negative electrode current collector, Cu and the active material lithium vanadium titanium phosphate were mixed in a volume ratio of 80 / 20, and then 100 parts of the obtained mixture was mixed and dispersed with 10 parts of ethyl cellulose as a binder and 50 parts of dihydroterpineol as a solvent to prepare a current collector layer paste.
[0085] (Preparation of intermediate layer substrate) The intermediate layer substrate was prepared by wet mixing the lithium vanadium phosphate powder prepared as the active material with the LZP-based Nasicon-type compound powder prepared as the solid electrolyte in a ball mill for 16 hours, dehydrating and drying the resulting powder, which was then calcined in a nitrogen-hydrogen mixed gas at 850°C for 2 hours. The calcined product was wet-pulverized in a ball mill, and then dehydrating and drying to obtain the intermediate layer substrate powder.
[0086] (Preparation of intermediate layer paste) The intermediate layer paste was prepared by adding 0.5 parts of filler (polyethylene), 15 parts of ethyl cellulose as a binder, and 65 parts of dihydroterpineol as a solvent to 100 parts of the intermediate layer base powder, and mixing and dispersing them.
[0087] (Preparation of external terminal paste) Silver powder, epoxy resin, and a solvent were mixed and dispersed to prepare a thermosetting external electrode paste.
[0088] Using these pastes, an all-solid-state battery of Example 1 was fabricated as follows.
[0089] (Fabrication of Positive Electrode Layer Unit) First, a 0.2 μm thick intermediate layer (referred to as the first positive electrode intermediate layer) was formed on the solid electrolyte layer sheet by screen printing, and dried at 80° C. for 10 minutes. Next, a 5 μm thick positive electrode active material layer (referred to as the first positive electrode active material layer) was formed on the solid electrolyte layer sheet by screen printing, and dried at 80° C. for 10 minutes. A 5 μm thick positive electrode current collector layer was further formed on the solid electrolyte layer sheet by screen printing, and dried at 80° C. for 10 minutes. A 5 μm thick positive electrode active material layer (referred to as the second positive electrode active material layer) was further formed on the solid electrolyte layer sheet by screen printing, and dried at 80° C. for 10 minutes. A 0.2 μm thick intermediate layer (referred to as the second positive electrode intermediate layer) was further formed on the solid electrolyte layer sheet by screen printing, and dried at 80° C. for 10 minutes. Next, a margin layer having a height approximately the same as that of the positive electrode layer was formed on the outer periphery of one end of the positive electrode layer by screen printing, and dried at 80° C. for 10 minutes. Next, the PET film was peeled off to obtain a sheet of the positive electrode layer unit.
[0090] (Fabrication of negative electrode layer unit) Next, a 0.2 μm thick intermediate layer (referred to as the first negative electrode intermediate layer) was formed on the solid electrolyte layer sheet by screen printing, and dried at 80° C. for 10 minutes. Next, a 5 μm thick negative electrode active material layer (referred to as the first negative electrode active material layer) was formed thereon, and dried at 80° C. for 10 minutes. A 5 μm thick negative electrode current collector layer was further formed thereon by screen printing, and dried at 80° C. for 10 minutes. A 5 μm thick negative electrode active material layer (referred to as the second negative electrode active material layer) was further formed thereon by screen printing, and dried at 80° C. for 10 minutes. A 0.2 μm thick intermediate layer (referred to as the second negative electrode intermediate layer) was further formed thereon by screen printing, and dried at 80° C. for 10 minutes, thereby preparing a negative electrode layer on the solid electrolyte layer sheet. Next, a margin layer having a height approximately the same as the negative electrode layer was formed on the outer periphery of one end of the negative electrode layer by screen printing, and dried at 80° C. for 10 minutes. Next, the PET film was peeled off to obtain a sheet of the negative electrode layer unit.
[0091] (Preparation of Laminate) A laminated substrate was produced by laminating multiple positive electrode layer units and negative electrode layer units alternately while offsetting one end of each unit so that they did not coincide. Furthermore, multiple solid electrolyte sheets were laminated as outer layers on both main surfaces of the laminated substrate to provide 200 μm outer layers. This was thermocompressed by a mold press, and then cut to produce an unfired all-solid-state battery laminate. Next, the laminate was de-bi-fired to obtain an all-solid-state battery laminate. The laminate was fired in nitrogen at a heating rate of 200 ° C / hour to a firing temperature of 1000 ° C, held at that temperature for 2 hours, and then naturally cooled before being removed. The filler became voids, and the voids had a long axis length of 0.5 μ m, a short axis length of 0.1 μ m, and an aspect ratio of 5.0.
[0092] (External electrode formation process) An external terminal paste was applied to the end faces of the laminate of the all-solid-state battery and thermally cured at 150°C for 30 minutes to form a pair of external electrodes.
[0093] The dimensions of the fabricated all-solid-state battery were approximately 4.5 mm x 3.2 mm x 1.1 mm.
[0094] The initial capacity and cycle characteristics of the prepared all-solid-state battery were obtained. The initial capacity and cycle characteristics were measured using a secondary battery charge / discharge tester. The voltage range was from 0.2V to 2.6V. First, as a pre-treatment, only the initial charge was performed at a constant current of 0.2C. Then, charge / discharge was performed to obtain cycle characteristics. Charging was performed at a constant current and constant voltage. Charging was performed at a current value of 0.2C, and after reaching 2.6V, it was terminated when the current value became 5% of the 0.2C current value. Discharging was performed under the condition of discharging at a current value of 0.1C. The cycle characteristics were evaluated as a capacity retention rate (%). The capacity retention rate (%) is the ratio of the discharge capacity after 100 cycles to the initial discharge capacity, with the discharge capacity at the first cycle being the initial discharge capacity. The capacity retention rate (%) is expressed by the following formula. Capacity retention rate (%) = ("Discharge capacity after 100 cycles" / "Discharge capacity at the first cycle") x 100
[0095] In addition, after measuring the initial capacity and the like, the all-solid-state battery was cut, and the area ratio of voids in the positive electrode active material layer and the negative electrode active material layer, the proportion of anisotropic voids in the voids, the shape of the anisotropic voids, the orientation direction of the anisotropic voids, and the area ratio of voids in the intermediate layer were determined.
[0096] (Examples 2 to 6) The difference from Example 1 is that the long axis length and the short axis length of the void were changed under the condition that the aspect ratio was constant. The aspect ratio was set to 5.0, the same as in Example 1. The long axis length, the short axis length and the aspect ratio of the void were adjusted by the shape of the filler added to the paste of the positive electrode active material layer and the negative electrode active material layer. In Examples 2 to 6, the same measurements as in Example 1 were performed.
[0097] (Examples 7 to 12) The difference from Example 1 is that the long axis length and the short axis length of the void were changed. The long axis length, the short axis length and the aspect ratio of the void were adjusted by the shape of the filler added to the paste of the positive electrode active material layer and the negative electrode active material layer. In Examples 7 to 12, the same measurements as in Example 1 were performed.
[0098] (Examples 13 to 18) The difference from Example 1 is that the short axis length of the void was fixed, and the long axis length and aspect ratio of the void were changed. The long axis length and aspect ratio of the void were adjusted by the shape of the filler added to the paste of the positive electrode active material layer and the negative electrode active material layer. In Examples 13 to 18, the same measurements as in Example 1 were performed.
[0099] (Example 19) A filler having a major axis length of 12.5 μm and a minor axis length of 1.1 μm was used, and a mesh was not used when preparing the paste for the positive electrode active material layer and the negative electrode active material layer. The other conditions were the same as in Example 1. The anisotropic voids in Example 19 were not oriented in a particular direction, and the major axis direction in each anisotropic void was random. In Example 19, the same measurements as in Example 1 were performed.
[0100] (Examples 20 to 24) A filler having a major axis length of 12.5 μm and a minor axis length of 1.1 μm was used, and the composition ratio of the active material particles and the filler in the paste of the positive electrode active material layer and the negative electrode active material layer was changed. The other conditions were the same as in Example 1. In Examples 20 to 24, the same measurements as in Example 1 were performed.
[0101] (Examples 25 to 28) Two types of fillers, a filler having shape anisotropy and a filler not having shape anisotropy, were used, and the mixing ratio between them was changed. The filler having shape anisotropy had a major axis length of 12.5 μm and a minor axis length of 1.1 μm. The other conditions were the same as in Example 1. In Examples 25 to 28, the same measurements as in Example 1 were performed.
[0102] (Example 29) This example differs from Example 21 in that the amount of filler added to the intermediate layer was changed to change the porosity of the intermediate layer. The other conditions were the same as in Example 21.
[0103] Comparative Example 1 This example differs from Example 1 in that a filler having a major axis length of 0.3 μm, a minor axis length of 0.3 μm, and an aspect ratio of 1.0 was used. The other conditions were the same as those of Example 1.
[0104] Comparative Example 2 This example differs from Example 1 in that a filler having a major axis length of 1.3 μm, a minor axis length of 1.3 μm, and an aspect ratio of 1.0 was used. The other conditions were the same as those of Example 1.
[0105] Comparative Example 3 This example differs from Example 1 in that a filler having a major axis length of 1.8 μm, a minor axis length of 1.1 μm, and an aspect ratio of 1.6 was used. The other conditions were the same as those of Example 1.
[0106] Comparative Example 4 This example differs from Example 1 in that a filler having a major axis length of 35.9 μm, a minor axis length of 1.1 μm, and an aspect ratio of 31.9 was used. The other conditions were the same as those of Example 1.
[0107] (Examples 1-2 to 22-2) All-solid-state batteries having a plurality of voids in all the insides of the side margin layer were produced as Example 1-2, Example 19-2, Example 20-2, Example 20-3, Example 20-4 and Example 22-2. As for other conditions, Example 1-2 was the same as Example 1, Example 19-2 was the same as Example 19, Examples 20-2 to 20-4 were the same as Example 20, and Example 22-4 was the same as Example 22. In addition, the side margin layers of the all-solid-state batteries of Example 1-2, Example 19-2, Example 20-2, Example 20-3, Example 20-4 and Example 22-2 have voids of the same configuration as the positive electrode active material layer and the negative electrode active material layer, except for the porosity, at the same ratio as Example 1, Example 19, Example 20 and Example 22, respectively. In addition, in Example 1-2, Example 19-2, Example 20-2, Example 20-3, Example 20-4 and Example 22-2, the porosity of the side margin layer was adjusted to be different from that of Example 1, Example 19, Example 20 and Example 22, respectively. In Example 1, Example 19, Example 20 and Example 22, the porosity of the side margin layer was less than 2%. In Table 2, the porosity of the side margin layer was added to Example 1, Example 19, Example 20 and Example 22 in Table 1, and they were written as Example 1-1, Example 19-1, Example 20-1 and Example 22-1. In Example 1-2, Example 19-2, Example 20-2, Example 20-3, Example 20-4 and Example 22-2, the same measurement as in Example 1 was performed, and the porosity of the side margin layer was further measured.
[0108] (Examples 101 to 128) As Examples 101 to 128, all-solid-state batteries were produced except for the step of forming the intermediate layer. That is, the all-solid-state batteries of Examples 101 to 128 did not have an intermediate layer. Other conditions for Examples 101 to 128 were the same as those for Examples 1 to 28, respectively.
[0109] (Comparative Examples 11 to 14) As Comparative Examples 11 to 14, all-solid-state batteries were produced without the step of forming the intermediate layer. That is, the all-solid-state batteries of Comparative Examples 11 to 14 did not have an intermediate layer. Other conditions for Comparative Examples 11 to 14 were the same as those for Comparative Examples 1 to 4, respectively.
[0110] The results of the initial capacity, cycle characteristics, void area ratio, ratio of anisotropic voids in the voids, shape of anisotropic voids, and orientation direction of anisotropic voids are shown in Tables 1 to 3 below. In Tables 1 to 3, the initial capacity is shown as a ratio when the initial capacity of Example 1 is taken as 100%. Table 3 shows the results of Examples 101 to 128 and Comparative Examples 11 to 14. The all-solid-state batteries of Examples 101 to 128 and Comparative Examples 11 to 14 do not have an intermediate layer. Therefore, the void area ratio in the intermediate layer was not measured in the all-solid-state batteries of Examples 101 to 128 and Comparative Examples 11 to 14.
[0111] [Table 1]
[0112] [Table 2]
[0113] [Table 3] [Explanation of symbols]
[0114] Reference Signs List 1...positive electrode layer, 1A...positive electrode current collector layer, 1B...positive electrode active material layer, 2...negative electrode layer, 2A...negative electrode current collector layer, 2B...negative electrode active material layer, 3...solid electrolyte layer, 4...laminated body, 5...first external terminal, 6...second external terminal, V, V2...plurality of voids, V1...anisotropic void
Claims
1. a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer; the positive electrode layer has a positive electrode current collector and a positive electrode active material layer in contact with the positive electrode current collector, the negative electrode layer has a negative electrode current collector and a negative electrode active material layer in contact with the negative electrode current collector, At least one of the positive electrode active material layer and the negative electrode active material layer has a plurality of voids therein, The plurality of voids have anisotropic voids having an aspect ratio, calculated by dividing the length in the major axis direction by the length in the minor axis direction, of 2 to 29, At least a portion of the side margin layers arranged adjacent to the positive electrode layer and the negative electrode layer on the outer periphery thereof has a plurality of voids therein, The plurality of voids in the side margin layer have anisotropic voids having an aspect ratio, calculated by dividing the length in the major axis direction by the length in the minor axis direction, of 2 or more and 29 or less.
2. a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer; the positive electrode layer has a positive electrode current collector and a positive electrode active material layer in contact with the positive electrode current collector, the negative electrode layer has a negative electrode current collector and a negative electrode active material layer in contact with the negative electrode current collector, At least one of the positive electrode active material layer and the negative electrode active material layer has a plurality of voids therein, The plurality of voids have anisotropic voids having an aspect ratio, calculated by dividing the length in the major axis direction by the length in the minor axis direction, of 2 to 29, a major axis direction of the anisotropic voids substantially coincides with an in-plane direction in which the positive electrode active material layer or the negative electrode active material layer extends.
3. The all-solid-state battery as described in claim 1, wherein 30% or more of the plurality of voids contained in the all-solid-state battery are anisotropic voids.
4. The average length of the anisotropic voids in the major axis direction is 0.2 μm or more and 40 μm or less, The all-solid-state battery according to any one of claims 1 to 3, wherein the average length of the anisotropic pores in the short axis direction is 0.1 µm or more and 5 µm or less.
5. 5. The all-solid-state battery according to claim 1, wherein a ratio of the plurality of voids in the positive electrode active material layer or the negative electrode active material layer is 3% or more and 30% or less.
6. an intermediate layer having ion conductivity between at least one of the positive electrode layer and the negative electrode layer and the solid electrolyte layer; The intermediate layer has a plurality of voids, The all-solid-state battery according to any one of claims 1 to 5, wherein the proportion of the plurality of voids in the intermediate layer is 0.1% or more and 8% or less.
Citation Information
Patent Citations
All-solid state battery
JP2012104270A
Negative electrode for all-solid battery
JP2017054720A
All-solid battery
JP2018206727A
All-solid-state cell
WO2013175993A1